Evaluasi Penerapan Program Bus Rapid Transit (BRT) Di Kota Tanjungpinang - Safitri, Ismi; Hendrayady, Agus; Kurnianingsih, Fitri (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2018)
This study aims to evaluate the performance of the implementation of the Tanjungpinang City Bus Rapid Transit (BRT) program. The method used in this study is a qualitative approach and type of descriptive research by presenting scientifically from the results obtained from the field through observation, interview and documentation techniques. There were 8 informants in the study. The location of this research is in Tanjungpinang City which is the operational area of BRT. Data analysis techniques in this study are data reduction, data presentation and conclusion drawing. The results of this study, namely the BRT program which has been running for approximately 7 months, has been running quite well and the program objectives have been achieved gradually, but there are some problems that have to be addressed, namely the lack of passengers from the community. know that BRT is public transportation and also due to the lack of socialization carried out only through the media, for the addition of BRT route routes that do not pass through the city route due to collision with the existing City transportation, the community is more crowded in the city area, and the last problem is delays in the disbursement of BRT's operational funds that become a barrier to the operation of the BRT, which requires costs for fuel and service per day.